VD_FINDINFO Plainte / 2020 / 13 vom 6. April 2020 - VD Tribunal cantonal (2020)
FICTION DE LA NOTIFICATION, CHOSE JUGÉE, MEILLEURE FORTUNE, EXÉCUTION DE LA SAISIE, MINIMUM VITAL | 265a LP, 34 al. 1 LP, 93 al. 1 LP